1989
DOI: 10.1038/340443a0
|View full text |Cite
|
Sign up to set email alerts
|

Association of class I major histocompatibility heavy and light chains induced by viral peptides

Abstract: We describe a cell in which association of a major histocompatibility complex class I heavy chain with beta 2-microglobulin is induced by a peptide derived from influenza nucleoprotein. Association of antigenic peptides with the binding site of class I molecules may be required for correct folding of the heavy chain, association with beta 2-microglobulin and transport of the antigen-MHC complex to the cell surface.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
502
1
2

Year Published

1993
1993
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 951 publications
(521 citation statements)
references
References 47 publications
16
502
1
2
Order By: Relevance
“…The egress of functional MHC class I complexes from the ER to the plasma membrane is dependent on the acquisition of peptide by a chain-b 2 M heterodimers [27][28][29]. Augmented chaperone activity may therefore influence the formation of stable MHC-peptide complexes by increasing the concentration of peptides available for binding MHC class I molecules within the ER.…”
Section: Discussionmentioning
confidence: 99%
“…The egress of functional MHC class I complexes from the ER to the plasma membrane is dependent on the acquisition of peptide by a chain-b 2 M heterodimers [27][28][29]. Augmented chaperone activity may therefore influence the formation of stable MHC-peptide complexes by increasing the concentration of peptides available for binding MHC class I molecules within the ER.…”
Section: Discussionmentioning
confidence: 99%
“…Two of these peptides, LNSVFDQL and TRVLNLGPI, were tested for their ability to bind to MHC class I molecules using an assay based on the peptide-induced stabilization and thereby increase of MHC molecules on the surface of RMA-S cells (H2 b haplotype) 30,31 . As expected, LNSVFDQL showed binding to H2-K b and TRVLNLGPI did assemble with H2-D b molecules (Supplementary Methods and Supplementary Fig.…”
Section: Isolation and Analysis Of Urinary Peptides By Mass Spectromementioning
confidence: 99%
“…The H chains associate with P 2 m shortly after synthesis in the endoplasmic reticulum (ER) [3]. Assembly of the H chain with p^m and peptide is required for conformational stability and presentation at the cell surface of peptides [4][5][6][7]. Proteins present in the cytosol appear to be cleaved into fragments of 8-11 amino acids [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have identified mouse and human cell lines, designated RMA-S [4], 721.174 [14] and 174CEM.T2 (T2) [15], which produce abundant cytoplasmic H chains and p^m, but present low amounts of surface MHC molecules. These so-called processing-defective cell lines are unable to present endogenously synthesized peptides to CTL [4,16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation